Heat treatment equipment for high-temperature and high-pressure resistant gate valve forgings - LIN WEIZHONG; CHEN WANZHU (2025)
The utility model discloses heat treatment equipment for a high-temperature-resistant and high-pressure-resistant gate valve forge piece, belongs to the technical field of gate valve forge piece machining, and solves the problems that an existing device can only drive the forge piece to revolve in a heating furnace, the forge piece cannot rotate, and the height of the forge piece is inconvenient to adjust, so that the forge piece is not fully heated. Supporting legs distributed in an annular array mode are fixedly installed on the bottom face of the base, a heating furnace is fixedly installed on the top face of the base, a hollow top base is fixedly installed on the top face in the heating furnace, and an adjusting assembly used for adjusting the position of a gate valve forge piece is arranged in the heating furnace. The motor drives the connecting column and the rotary disc at the bottom of the connecting column to rotate, the containing barrel and forgings in the containing barrel can be driven to revolve